CHALLENGES AND OPPORTUNITIES TO DESIGN FUTURE CROPS: GATEWAY TO SUSTAINABLE AGRICULTURE IN 21ST CENTURY - AMIN, HAB; ULLAH, S; MAHDI, SAH; REHMAN, HU; KAUSAR, R; SHAMIM, F; ALI, S; KOHLI, SA; LATIF, A; SHAHZADI, N; ALVI, A (Biological and Clinical Sciences Research Journal, 2024)
The global food production system is facing numerous challenges due to factors such as population growth, climate change, limited resources, and environmental preservation. To address these challenges, various strategies can be employed to develop future crops that are more productive, nutritious, and resilient. One strategy is to improve the yield potential of existing crops by developing new high-yielding cultivars. This can be achieved through the development of new varieties that can produce more grain under optimal conditions. Additionally, improving the nutritional quality of crops is important to address nutrient deficiencies. Synthetic biology and metabolic engineering methods can be used to develop crops with enhanced nutritional value. Efficient utilization of agricultural resources is another important aspect of crop improvement. This includes developing crops that use water and nutrients more efficiently, reducing the need for irrigation and fertilizers, and minimizing environmental impacts. Increasing the resistance of crops to pests, diseases, and extreme weather events can also help reduce the use of pesticides and minimize crop losses. The domestication of wild or semi-wild plants through genetic manipulation offers new opportunities for crop design. These plants may have high nutritional value, stress tolerance, and specialized metabolites that can be incorporated into cultivated crops. Similarly, the domestication of orphan or neglected plants can contribute to crop improvement by incorporating unique traits. Genetic improvement through the transfer of genes from wild relatives or other species can also enhance crop productivity. Advancements in genomics and genetic technologies can aid in the identification and transfer of beneficial alleles. Agronomic improvements, such as maximizing the effectiveness of crop protection agents and fertilizers while minimizing their environmental impact, can also contribute to crop performance. The emerging field of synthetic biology offers opportunities for developing novel biological devices and systems that can further enhance crop productivity and resilience. Overall, these strategies can help address the challenges faced by the global food production system.